Collaboration between designers and contractors to improve building energy performance. (10th May 2019) - Xu, Xiaoxiao; Li, Clyde Zhengdao; Wang, Jiayuan; Huang, Wenke
Abstract: Improvement of building energy performance is crucial in achieving energy conservation goals. Previous studies have indicated that effective collaboration among stakeholders can help to address the building energy performance gap. However, only a few studies have examined the effects of underlying collaboration between designers and contractors. To fill this research gap, this study proposes an evolutionary game model to investigate the underlying logic of the collaboration by analyzing the dynamic behaviors of designers and contractors. First, the main possible drivers and barriers of the collaboration between designers and contractors were identified through a literature review and an expert interview. Second, a Nash equilibrium model was utilized to analyze the decision of designers and contractors under different scenarios. The results show that the best means to promote the collaboration is "reducing collaboration costs", followed by "increasing the collaboration benefits" and "decreasing the loss caused by a lack of collaboration". Based on the parameter discussion of the evolutionary game model, five solutions were proposed for the effective collaboration between designers and contractors. This study helps to clarify the dynamic collaboration decision process of designers and contractors, who are considered players with bounded rationality. The proposed evolutionary game model provides a theoretical basis for quantitative research on the collaboration between designers and contractors. This study could help researchers to consider the dynamics of collaboration among stakeholders in building projects, and it could also help practitioners to select proper strategies for improved collaboration. Graphical abstract: Image 10481961